2018
DOI: 10.1053/j.gastro.2018.03.064
|View full text |Cite
|
Sign up to set email alerts
|

Female-Specific Association Between Variants on Chromosome 9 and Self-Reported Diagnosis of Irritable Bowel Syndrome

Abstract: In a sufficiently powered GWAS of IBS, we associated variants at the locus 9q31.2 with risk of IBS in women. This observation may provide additional rationale for investigating the role of sex hormones and autonomic dysfunction in IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 52 publications
5
60
0
4
Order By: Relevance
“…In order to explore this hypothesis, we tested the rs7940681 SNP for association with IBS in a meta‐analysis of association data extracted from 2 large genome‐wide association studies recently published by Bonfiglio et al . (47, 48): as shown in Table 4 , the A allele allowing Gli binding and repression at the ANO1 promoter was also weakly but significantly associated with small effects on IBS risk in this analysis.…”
Section: Resultssupporting
confidence: 54%
“…In order to explore this hypothesis, we tested the rs7940681 SNP for association with IBS in a meta‐analysis of association data extracted from 2 large genome‐wide association studies recently published by Bonfiglio et al . (47, 48): as shown in Table 4 , the A allele allowing Gli binding and repression at the ANO1 promoter was also weakly but significantly associated with small effects on IBS risk in this analysis.…”
Section: Resultssupporting
confidence: 54%
“…Blocking dopamine D2 receptors encoded by this gene in the chemoreceptor trigger zone relieves 23 nausea and in the gastrointestinal tract increases motility 61 . A previous study reported that rs10512344 is the 24 only one SNP genome-wide significantly associated (P = 3.6E-8) with IBS using UKB data 20 . Both the IBS (lead 25 SNP: rs112243849, P = 7.5E-8) and IBS + M (lead SNP: rs7861675, P = 1.2E-7) phenotypes in our study 26 reconfirmed the association between this locus and IBS at the genome-wide suggestive level.…”
Section: Introductionmentioning
confidence: 96%
“…These loci implicate pathways such as 28 autophagy and the IL-17/IL-23 axis and provide insights into IBD pathogenesis 15 . While IBD has been 1 extensively studied through the GWAS paradigm, only a few GWASs for GORD 16 , PUD 17 and IBS [18][19][20] have been 2 conducted to date, most of which were under-powered. 3Here, we aim to identify genetic susceptibility factors for GORD, PUD, IBS using the genome-wide 4 association study (GWAS) paradigm.…”
mentioning
confidence: 99%
“…Impaired baroreflex pathways have been found in familial dysautonomia [31], which is not supported in our cohort with a very low prevalence of orthostatic hypotension. The found association between gene mutations of IKBKAP and self-reported IBS may reflect that many patients with GI symptoms are not properly examined [15], and could have other diagnoses of autonomic dysautonomia with secondary GI symptoms [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…The autonomic dysfunction previously described in IBS may rather be a secondary response to peripheral and/or central hypersensitization [4,13,14], than of primary, etiological importance. On the other hand, genetic studies have shown associations between IBS and gene variants of locus 9q31.2, including IKBKAP [15], gene variants found in patients with familial dysautonomia, who also express a high prevalence of GI symptoms [16].…”
Section: Introductionmentioning
confidence: 99%